TINJAUAN PENAMBAHAN ADITIF MINERAL ABU TERBANG TERHADAP KETAHANAN BETON PADA LINGKUNGAN AGRESI SULFAT - Ernawati Sri Sunarsih (Indonesian Journal Of Civil Engineering Education, 2017)
The research aims to determine ( 1) the wede168 increase of compressive strength of concrete with addition of fly ash to be compared to normal concrete ( 2) the resistant of normal concrete and also concrete with fly ash mineral additive in 2%, 5% and 7% sulphuric acid solutions, and ( 3) the resitant of concrete with fly ash mineral additive with the increase of concentration of sulphuric acid solution in comparing normal concrete.The method employed in this research was experimental method, by preparing the test object constituting the concrete cylinder with Æ 150 mm and 300 mm height for the compressive strength test. With the percentage of fly ash addition are 0%, 20%, 30% and 40% from requirement cement and qualities of designed concrete is 22,5 MPa. Amount of object test to the each condition is 4. To know concrete resistant in sulphate aggression environment, hence conducted by immersied of concrete in sulphuric acid solutions with concentration 2%, 5% and 7% during 30 days.From the research, it can be found that: ( 1) the addition of fly ash into fresh concrete will improve compressive strength of concrete. At addition fly ash 20% from requirement cement, compressive strength of  concrete increase 23,39%. For the addition of fly ash 30% and 40%, the increase of compressive strength concrete were 21,54 % and 0,31%. While in optimum percentage of fly ash addition is 23,46% (2) the immersied concrete in sulphuric acid solution result degradation compressive strength of concrete. At the same concentration of sulphuric acid solution, concrete with fly ash additive mineral have resistant which is better to be compared to normal concrete. This seen [at] percentage of compressive strength degradation of fly ash concrete which is smaller to be compared to normal concrete. Equally the percentage of compressive strength degradation inversely proportional with the percentage of fly ash addition ( 3) the increase of concentration of sulphuric acid solution will be result of aggression that happened at ever greater. If compared to normal concrete, concrete with fly ash in the reality more effective if used at high concentration of sulphuric acid solution. This matter can be seen from difference of percentage of compressive strength degradation ever greater at the height of concentration of sulphuric acid solution.